Lecturer Intentions in Teaching Tax Awareness: A Study of the Theory of Planned Behavior - Nyoman Trisna Herawati; Luh Gede Kusuma Dewi; Made Ary Meitriana (Jurnal Akuntansi dan Perpajakan, 2023)
The application of tax inclusion in higher education through compulsory courses or MKWU requires the readiness of the lecturers themselves. For this reason, this study aims to analyze the intentions of MKWU lecturers in teaching tax awareness materials to increase tax inclusion. The lecturer's intention, seen from the perspective of the theory of planned behavior consist of attitude toward the behavior, subjective norm, and perceived behavioral control. The research method uses a quantitative approach with multiple regression analysis techniques. Respondents in this study were MKWU lecturers at Undiksha with a sample of 40 people. Data were collected through a questionnaire with a 5-point Likert scale. The results showed that the lecturers' intention to teach tax awareness was high. Furthermore, the attitude variable has a positive and significant effect on lecturers' intentions in teaching tax awareness, while subjective norm and perceived behavioral control have not a significant effect.